Effects of Work Ability and Motivation on Employee Productivity in North Jakarta Manufacturing Firm Study - Ade Solihin; Sabil Sabil (Penerbit Goodwood, 2025)
Purpose: This study examines how work ability and work motivation shape employee work productivity at PT Gautama Indah Perkasa, a manufacturing firm in North Jakarta, Indonesia, a setting where fluctuating output has pushed management to look for evidence-based grounds for its human resource decisions. Methodology: A quantitative, descriptive survey was conducted among the firm's 50 permanent employees. A saturated sampling approach produced 36 usable responses. Work ability, work motivation, and work productivity were each measured with Likert-scaled instruments whose validity and reliability were confirmed through corrected item-total correlation and Cronbach's Alpha, after which classical assumption tests preceded a multiple linear regression run in SPSS 23.Results: All twenty-three items were valid and every construct was reliable. The fitted equation, Y = 6.128 + 0.287X1 + 0.343X2, shows that work ability carries a significant partial effect (B = 0.287, t = 2.971, p = .006) while work motivation's partial effect, though positive, falls short of significance (B = 0.343, t = 1.680, p = .102). Jointly, the two predictors explain 40.4 percent of productivity variance and are simultaneously significant (F = 11.175, p = .000). Conclusions: Work ability stands out as the dependable, individually significant driver of productivity in this factory, whereas motivation contributes mainly through its combined effect with ability.Limitations: A single-firm, cross-sectional design with only 36 respondents restricts generalizability and causal claims. Contributions: The study offers Indonesian manufacturing HR practitioners a concrete basis for prioritizing competency-building investment over purely motivational programs.